Knowledge, attitude, and practice of care providers about congenital rubella syndrome - Ravaoarisoa, Lantonirina; Andriatahina, Todisoa N.; Randriananahirana, Zina A.; Ranivoson, Andrianina H.; Rahajamanana, Vonintsoa L.; Andriamahita, Jocelyn; Andrianirinarison, Jean C.; Robinson, Annick L. (International Journal of Research in Medical Sciences, 2020)
Background: Behaviour of healthcare providers when facing an illness is an important part of their struggle. The aim of this study was to assess the level of knowledge, the attitude and the practice of health care providers regarding to the Congenital Rubella Syndrome. Methods: Authors did a descriptive study on the knowledge, the attitude and the practice of healthcare providers about Congenital Rubella Syndrome with 161 healthcare providers working in 8 hospitals in Madagascar. A self-introduced survey was used to collect the data. Results: There were 87% of all healthcare providers included in the study, who said that rubella in the first trimester of pregnancy was the cause of this syndrome for child, 87% knew at least 2 of the 3 major signs of Congenital Rubella Syndrome and more than 80% had a good knowledge of the criteria for diagnosing cases (suspected, clinically confirmed, laboratory confirmed). The referral to a hospital or to a specialist was the most proposed for the management of the case of Congenital Rubella Syndrome. The prescription of an IgG avidity for rubella and advising abortion were the main propositions for mothers having a positive test at the first trimester of pregnancy. Conclusions: A fairly satisfactory level of knowledge of healthcare providers was noted.